Ponderomotive processes as proxies for breaking of ion acoustic solitary waves - Kakad, Amar; Kakad, Bharati (My University, 2016)
Wave breaking is a ubiquitous nonlinear phenomenon in plasma that is followed by sudden drop of wave amplitude after a wave steepening. We perform fluid simulation of the ion acoustic solitary waves (IASWs) to investigate the start time of the wave steepening and breaking process. This simulation demonstrates that a long wavelength perturbation in the electron and ion equilibrium densities evolves into two long wavelength IASWs. These IASWs steepens and breaks into short wavelength solitary structures, which become stable ion acoustic solitons at later time. From the detailed analysis of simulation output, we accomplish the criteria for steepening and breaking of the IASWs based on the (a) acceleration of IASWs (b) balance between maximum potential energy and the maximum electron kinetic energy. Furthermore, we examined the ponderomotive potential and the ponderomotive frequency of the electrons and ions during the process of the generation, steepening and breaking of these IASWs. It is observed that the maximum ponderomotive potential of both electrons and ions enhances during the steepening and attains the maximum close to the breaking of the IASWs. The simulation shows that the electron (ion) average ponderomotive frequency is considerably higher than the electron plasma frequency in the initial phase of generation of IASWs, which rapidly oscillates and approaches to frequencies much smaller than electron (ion) plasma frequency. These ponderomotive frequencies remain unchanged until the start of steepening of the IASWs; however, both frequencies are found to increase during the steepening and breaking of these IASWs. Based on this information, we propose that the ponderomotive potential and ponderomotive frequencies of electrons and ions can be used as proxies to determine the steepening and breaking time of the IASWs. We find that the onset time of the wave breaking varies inversely with the thermal velocity of the electrons and the amplitude of the initial density perturbation (IDP), while it is directly proportional to the width of the IDP. It is also noted that the number of solitons formed in the system and their characteristics depends on the electron temperature, width, and amplitude of the IDP.
Keywords: Acoustic solitary waves; Ponderomotive processes; Ion acoustic solitary waves